Integrating innovation : South Australian entrepreneurship systems and strategies - Roos, Göran; O'Connor, Allan (The University of Adelaide, University of Adelaide Press, 2015)
Entrepreneurship can be taken as a study of the entrepreneur and new business creation. However, this conception of entrepreneurship misses the critical link to economic outcomes; the ebb and flow of social and economic fortunes that are underpinned by the actions, reactions and engagement of individuals in a specific social and economic system that brings about innovation and change. In this book the authors are exploring how the linkages within the system can be conceptualised and made transparent.